ЦЕНЗУРА В СОВРЕМЕННОЙ ИСТОРИИ ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article is devoted to censorship in the modern history of cinematography, an analysis of the current state of censorship in the history of cinema